Evaluación de pH, concentración de FeSO4 y FeCl3, en la remoción de sólidos suspendidos y sulfuros en efluentes de pelambre en curtiembres - Montoya Arias, Christina Elizabeth (2017)
The objective of this research was to evaluate the influence of pH, concentration of ferrous sulfate (FeSO4) and ferric chloride (FeCl3), as well as the concentration and type of flocculants in the removal Suspended solids and sulphides in effluent from the fur stage from the "Ecológica del Norte SA" tannery. The most suitable values of the variables were determined by the jar test method, since it allowed to determine the optimum pH, optimum coagulant concentration as well as the concentration and type of optimum flocculant in the coagulation-flocculation process for water treatment Residues of the fur stage from the tannery "Ecológica del Norte SA". Ferric chloride (FeCl3) and ferrous sulfate (FeSO4) were used as coagulants in combination with both the anionic, polyacrylamide, quaternary amine and cationic flocculant flocculants, respectively. With the optimum coagulant pH and concentration values, the best concentration and flocculant rate for the coagulation-flocculation process was evaluated according to percentages of removal in turbidity, suspended solids, total solids, chemical demand for oxygen and sulfides. The optimum pH at which the coagulation process (in the range of 9.00 to 12.40) can be performed was found to be the optimum pH of 9.00 and the best dose of FeSO4 (range between 10000 and 20000 mg/L) and FeCl3 (Range between 6000 and 9000 mg/L) and at optimum pH in the coagulation process. Finally, it was established that the best combination between coagulant and optimum flocculant was at pH 9.00, with a concentration of ferric chloride of 7000 mg/L and anionic flocculant concentration of 50 mg/L with which a turbidity removal of 82.22%, Total solids of 75.63%, suspended solids of 95.46%, chemical demand of oxygen of 98.41% and sulfides of 99.89%. It also generated a treatment cost of 27.84 nuevos soles/m3 of treated effluent